2017
DOI: 10.1007/s11255-017-1696-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a family history of prostate cancer on the prognosis and features of the disease in Korea: results from a cross-sectional longitudinal pilot study

Abstract: A family history of prostate cancer seemed to have no effect on prognosis and disease aggressiveness. However, this study proposed a rationale for performing earlier prostate-specific antigen testing in men with a family history of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Research from Sweden demonstrated that around 11.63% of PCa were familial . However, Lee et al reported that only 3.8% of PCa patients had positive FH in South Korea . Our study based on Chinese population shows similar positive rate of FH (4.5%) as that in South Korea.…”
Section: Discussionsupporting
confidence: 69%
“…Research from Sweden demonstrated that around 11.63% of PCa were familial . However, Lee et al reported that only 3.8% of PCa patients had positive FH in South Korea . Our study based on Chinese population shows similar positive rate of FH (4.5%) as that in South Korea.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, family history had no prognostic effect on biochemical failure. However, our previous study confined the study population to those who have undergone radical prostatectomy [19]. Therefore, the prostate cancer was more aggressive in those group compared to the study population in this study and this might be the reason why the family history was reported as significant predictor of clinically significant prostate cancer with higher Gleason scores only in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, a positive family history was associated with aggressive features of the disease at diagnosis. However, our group previously reported that the presence of a family history was not identified as a prognostic factor of overall survival for prostate cancer among Korean population [19]. Additionally, no statistically significant differences were found in several parameters, including the Gleason score and pathologic stage, tumour volume, and positive surgical margin, between patients with and without a family history.…”
Section: Discussionmentioning
confidence: 87%
“…The individual relative risk of a PCa diagnosis is doubled in first-degree male relatives of PCa patients [2], and 10-20% of PCa patients are reported to have a positive family history among their first-degree relatives [3]. Although numerous studies have focused on the clinicopathological features associated with family history of PCa [4][5][6], clinical observation has shown no substantial differences between PCa patients with family history and those without, except that family history is associated with younger age at diagnosis [2]. Recent findings point to genetic factors that underlie familial aggregations of PCa; genetic differences between patients with and without family history of PCa can be based on single-nucleotide polymorphisms or germline mutations, including HOXB13, BRCA1, BRCA2, and MLH1, which are associated with an increased risk of familial PCa [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%